2009
DOI: 10.2214/ajr.09.3122
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Sonographic Classification of Axillary Lymph Nodes in Patients With Breast Cancer: Node-to-Node Correlation With Surgical Histology and Sentinel Node Biopsy Results

Abstract: Sonographic classification of axillary lymph nodes is effective for predicting the presence of metastases to avoid sentinel node biopsy or to reduce unsuccessful lymphatic mapping during sentinel node biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 24 publications
2
98
1
6
Order By: Relevance
“…6 Diagnostic ultrasound imaging (US) has been used to evaluate lymph nodes (LNs) for both benign disease as well as metastases. [12][13][14] It has also been found to be a valuable method to guide LN biopsies. 15,16 Although gray scale US, color flow US, and pulsed Doppler imaging have been used alone or in combination to assess LNs for the presence of metastases, US cannot be used for lymphatic mapping (ie, to identify a tumor's SLNs) because mapping requires administration of a tracer (eg, dye or radiopharmaceutical).…”
mentioning
confidence: 99%
“…6 Diagnostic ultrasound imaging (US) has been used to evaluate lymph nodes (LNs) for both benign disease as well as metastases. [12][13][14] It has also been found to be a valuable method to guide LN biopsies. 15,16 Although gray scale US, color flow US, and pulsed Doppler imaging have been used alone or in combination to assess LNs for the presence of metastases, US cannot be used for lymphatic mapping (ie, to identify a tumor's SLNs) because mapping requires administration of a tracer (eg, dye or radiopharmaceutical).…”
mentioning
confidence: 99%
“…Lymph node dissection may be avoided in cases where the sentinel lymph node is not located, either in obese patients or those with afferent lymphatic vessel congestion by tumor cells (18,25). In addition, the adverse effects of sentinel lymph node mapping, including pain, loss of sensitivity and lymphedema of the upper limb may be prevented (7,18,19). Nevertheless, despite the results of the present study revealing specificity of cytology similar to the SNB, the sample size of this study was small and there is a requirement for further studies with larger sample sizes to improve the analysis of results.…”
Section: Discussionmentioning
confidence: 99%
“…Oz et al (5) revealed that a cortical thickness >4.0 mm had a sensitivity of 86% and specificity of 87%, whereas at the cut-off point of 3.0 mm, specificity decreased to 37%. However, results in the literature are heterogenous, as ultrasonographic examination is operator-dependent and machine-dependent and there is a great variation in sensitivity and specificity when only US is used for evaluation of axillary lymph nodes (18)(19)(20). By contrast, using US-guided FNA, certain authors have demonstrated a sensitivity and specificity ranging from 42.…”
Section: Introductionmentioning
confidence: 99%
“…In our study cortical thickness cutoff at 2.3 mm gives sensitivity and specificity of 86% and 47%. Cortical thickness has been evaluated by Cho et al (2009) and has evaluated 191 lymph nodes from breast cancer patients. When the cutoff point of a cortical thickness of 2.5 mm was used, sonographic classification showed 85% (35/41) sensitivity, 78% (117/150) specificity.…”
Section: Benign Vs Metastasis (Table3 Figure3)mentioning
confidence: 99%
“…If a malignant node is diagnosed by ultrasono guided fine needle aspiration, then the patient can avoid the sentinel node procedure and can proceed to full axillary node dissection at the time of primary tumor surgical resection. However in many centers lack of sentinel node procedure, axillary lymph node dissection (ALND) is performed routinely in cases of invasive breast cancer (Cho et al, 2009). Axillary lymph node dissection is a costly procedure associated with various side effects such as paresthesia, hematoma, seroma, restricted shoulder motion and lymphedema.…”
Section: Introductionmentioning
confidence: 99%